Structural higher education reform - design and evaluation: synthesis report - European Commission (Publications Office of the European Union, 2016)
This study analyses how different types of system-level (or ‘landscape’) structural reforms in higher education have been designed and implemented in selected higher education systems. In the 12 case studies that form the core of the project, the researchers examine reforms aimed at: - Increasing horizontal differentiation between different types of higher education institutions (for example reforms to introduce or modify the role of universities of applied science); - Increasing vertical differentiation through increasing or decreasing positional or status differences between higher education institutions (for example, reforms aimed at concentrating research in a limited number of universities) and; - Changing institutional interrelationships between higher education institutions (for example, through mergers, the formation of associations of institutions). In each case, the researchers set out to understand the origins and objectives of the reforms examined, the why they were designed and implemented, the extent to which they achieved their objectives and the factors affecting success or failure. The overall objective is to provide policy makers at the European, national and institutional levels with policy relevant conclusions concerning the design, implementation and evaluation of structural reforms